2006
DOI: 10.1177/0013161x06289962
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Choices Within Market Constraints: Re-Visioning Access to and Participation in the Superintendency

Abstract: Purpose: In this article, the authors highlight three constraints—structural time crisis (Schor, 1991) ideal worker norms (Williams, 2000), and labor and occupational queues (Reskin & Roos, 1990; Strober, 1992)—on the decisions and choices of women seeking to advance to and hold positions in the superintendency. Proposed Conceptual Argument: The authors contribute to and extend the extant body of work by integrating a conceptual framework that emerges from feminist economics theory and feminist organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…career PaThs anD TiMe PriOr TO The sUPerinTenDencY A number of studies highlight the fact that women enter the superintendency later than their male counterparts because they spend more time in the classroom and in intermediate positions (Ortiz, 1982;Heilbrun, 1988;Shakeshaft, 1989;Gupton, 1998;Glass, 2000;Tallerico and Blount, 2004;Björk and Kowalski, 2005;Grogan and Brunner, 2005;Mahitivanichcha and Rorrer, 2006;Kowalski et al, 2011). For respondents to the 2015 MidDecade Survey, 69.3% were 51 or older (the median age for white women was 55 years, while for women of color, the median age was 51 years).…”
Section: The History Of the Representation Of Women In The Superintenmentioning
confidence: 99%
“…career PaThs anD TiMe PriOr TO The sUPerinTenDencY A number of studies highlight the fact that women enter the superintendency later than their male counterparts because they spend more time in the classroom and in intermediate positions (Ortiz, 1982;Heilbrun, 1988;Shakeshaft, 1989;Gupton, 1998;Glass, 2000;Tallerico and Blount, 2004;Björk and Kowalski, 2005;Grogan and Brunner, 2005;Mahitivanichcha and Rorrer, 2006;Kowalski et al, 2011). For respondents to the 2015 MidDecade Survey, 69.3% were 51 or older (the median age for white women was 55 years, while for women of color, the median age was 51 years).…”
Section: The History Of the Representation Of Women In The Superintenmentioning
confidence: 99%
“…Björk and Keedy (2001) also found that board members' perceptions that women are not as competent as men prevented female applicants from obtaining superintendency. Mahitivanichcha and Rorrer (2006)'s study provided further evidence that male-dominant boards included members who held reluctant attitudes toward hiring women as superintendents. They claimed that a more diverse board would hire diverse candidates.…”
Section: The Hiring Process and Institutional Barriersmentioning
confidence: 93%
“…Women face challenges in obtaining and maintaining managerial positions in education and the "professional challenges of women superintendents have been the subject of research in the last three decades" (VanTuyle & Watkins, 2009, p. 135). As Mahitivanichcha and Rorrer (2006) have argued, in spite of having the desire and qualifications, women face challenges in gaining access to and then performing educational leadership positions.…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations